The SADC protocol on trade in services : a review of the protocol in light of the GATS and other SADC protocols and what it means for trade in services in the region - Ngubula, Moyombuya (School for Legal Practice, 2015)
In 1995 the General Agreement on Trade in Services (GATS) came into force. This is the World Trade Organization’s (WTO) legal instrument aimed at regulating multilateral trade in services (TiS). GATS was negotiated in light of the increase in TiS in the world and the need to regulate this area of trade. Prior to GATS coming into force, only trade in goods was regulated at the multilateral level through the General Agreement on Trade and Tariffs (GATT). There are many benefits that come along with TiS and there is a need for developing countries to open up their service markets. Liberalised TiS in developing countries can bring about technological advancement, it enhances competition, it creates employment and it enhances productivity. Opening up the services sector brings about more service suppliers into the economy. The increase in service suppliers means that there will be competition and competition eliminates inefficiency and gives consumers access to a variety of services at low prices. The service areas that SADC countries have comparative advantage in such as tourism and transport are labour intensive, the opening of such sectors will therefore be employment creating across the region. In more technologically complex service areas (like telecommunications) the liberalisation of such sectors allows those countries that trade in such services to spill-over the technical know-how to other countries in the region. Among some of the provisions of GATS that regulate TiS are provisions that define services, identify services areas and modes of trading in services. GATS provides for member states to accord treatment no less favourable than that they give to their services and service suppliers to services and service suppliers that come from other members (MFN treatment). Services from members are also to be afforded national treatment when traded in the territory of another member. The national treatment afforded to services differs from that in GATT in that unlike in GATT national treatment under GATS only comes about as a result of specific commitments made by each member. There are some exceptions to the general rules of GATS. One such exception allows for the establishment of a preferential trade agreements to regulate TiS in a region. In terms of Article V member states can enter into preferential trade agreements to regulate their TiS. The preferential trade agreements established in terms of Article V allow the parties thereto to extend more favourable conditions to the services and service suppliers from the countries that are member states without extending them to the rest of the WTO members.0 In order to satisfy Article V it must be shown that the agreement in question covers a substantial number of sectors and that it eliminates or provides for the substantial elimination of discrimination. There is some flexibility that is however afforded to preferential agreements entered into by developing countries in so far as the elimination of discrimination is concerned. SADC is a Regional Economic Community that was established in 1992 in terms of the SADC Treaty. The SADC treaty provides for the regulation of trade.14 It also provides for the concluding of Protocols when the need arises. In light of the provisions of the treaty and of GATS Article V, SADC recently concluded the SADC Protocol on Trade in Services (SADC TiS Protocol). The Protocol is aimed at liberalising substantial TiS in the Southern African region while at the same time ensuring that the treaty remains consistent with other Protocols that precede it. In light of the provisions of GATS the paper will carry out an analysis of the SADC TiS Protocol. The paper will consider the requirements that GATS places on preferential agreements and assess how far the SADC TiS Protocol goes in satisfying the requirements.